Coordination of Counteraction to Turmoil in the Economic Space of the Black Sea Region - Yefymenko, T.I. (Science and Innovation, 2024)
Introduction. The scientific substantiation of the updated institutional framework for the interaction of the countries of the Black Sea Economic Cooperation Organization (BSEC) in the context of its gradual transformation into a multilateral integration structure is an urgent issue of today, since in the new reality there are threatening tendencies of market imbalances due to geopolitical factors, higher destabilization risks in the economic activity space. Problem Statement. The current state of the hybrid world order is accompanied by restructuring international, state and social institutions. Manifestations of uncertainty, conflicting relationships in the Black Sea countries complicate the implementation of European integration reforms aimed at supporting sustainable development. Purpose. To Identify the most urgent areas of necessary social transformations in the BSEC countries, taking into account sovereign interests regarding possible external and internal threats and impacts. The economic sphere primarily involves such issues as ensuring employment, solvency of participants in contractual relations, etc. Materials and Methods. The systematic approach, sequential processing of interconnected trends of statistical indices and methods of situational analysis and synthesis are used for the analysis. Results. The ways of strengthening counteraction to the destabilization of region's economy are shown. Considering its strategic role, it has been proposed to focus on the issues of shaping the future, taking into account the principle of the coordination of scenarios and actions of the BSEC countries. Conclusions. Collaboration of global and regional players aimed at common strategic thinking, must be focused on finding the means and tools to transform the Black Sea from the zone of confrontation into the space for the peaceful convergence of the values of civilization. It is worth harmonizing consistent efforts aimed at reducing territorial tensions with the comparatively low rates of societies’ perception of the need for appropriate reforms on implementing the sustainable development goals.